Role of Concurrent use of Thoracic Ultrasonography with 2D Echocardiography among Patients with Commonly Diagnosed Respiratory Illnesses: A Cross-sectional Study - Amrutha Peter; Jitendra Kishor Bhargava; Amit Kinare; Rekha Agrawal; Brahma Prakash (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Respiratory diseases may affect the functioning of the heart, lung and heart work synchronously. Clinical assessment and work-up of patients with pulmonary problems may need an extension to cardiac disease. Thoracic Ultrasonography (TUS) is a diagnostic modality being used to assess respiratory conditions as it carries the inherent advantages of ultrasonography such as being reliable, inexpensive, safe, reproducible, and having no radiation hazard. Aim: To assess the usefulness of performing Thoracic Ultrasound (TUS) and 2D Echocardiography in the same sitting, so as to confirm the respiratory diagnosis and to early identify various cardiac dysfunctions in patients with respiratory illnesses. Materials and Methods: This cross-sectional study was conducted in the Outpatient Department (OPD) of Respiratory Medicine at Netaji Subhash Chandra Bose Medical College (tertiary care hospital), Jabalpur, Madhya Pradesh, India, from January 2019 to March 2020. Patients hospitalised with clinico-radiological diagnosis of pleural effusion, pneumonia, pulmonary fibrosis of interstitial lung disease, pulmonary oedema and Chronic Obstructive Pulmonary Disease (COPD) were subjected to TUS and echocardiography. Sonological findings and cardiac abnormalities were recorded. Data was analysed by applying descriptive statistics, t-test, and Chi-square test. A p-value <0.05 was considered as statistically significant. Results: A total of 133 patients were enrolled with diagnosis of pleural effusion (n=46), COPD (n=33), pneumonia (n=22), pulmonary fibrosis (n=18) and pulmonary oedema (n=14). Out of total 46 patients, 36 patients with pleural effusion had cardiac findings. The presence of pleural effusion showed a significant association with cor-pulmonale (p-value=0.012), dilated Right Ventricle (RV) (p-value=0.012), septal deviation (p-value=0.012), Pulmonary Hypertension (PH) (p-value=0.0002), Left Ventricular (LV) dysfunction (p-value=0.02) and Left Ventricular Ejection Fractions (LVEF) (p-value=0.006). The focal B-lines were seen in patients with pneumonia. Patients with Pulmonary fibrosis had scattered B-Lines, and patients with pulmonary oedema had bilateral diffuse B-lines. Among patients with pulmonary fibrosis, 11 (61.1%) had cor-pulmonale and dilated RV, whereas 10 (55.5%) had septal deviation. Patients with scattered B-lines more commonly had PH. In patients with COPD, cor-pulmonale was detected in 21 (63.6%), LV dysfunction in 5 (15.1%), mild PH in 14 (42.4%), moderate PH in 7 (21.2%), and severe PH in 5 (15.1%) using echocardiography. Conclusion: This study reveals the importance of performing a combination of TUS with 2D Echocardiography and suggests its usefulness in early diagnosis of cardiac dysfunctions in patients with various respiratory illnesses.